Role of Early Biopsy in the Diagnosis of Oral Squamous Cell Carcinoma (Academia Journal of Medicine, 2026)
Aim:The aim of this study was to evaluate the role of early biopsy in the diagnosis of oral squamous cell carcinoma (OSCC) and to assess its importance in the early detection of suspicious oral lesions. Methodology:This retrospective descriptive study included 120 patients who presented with clinically suspicious oral lesions and underwent biopsy for histopathological evaluation. Clinical records were obtained from the departmental archives of Oral Medicine and Radiology / Oral and Maxillofacial Pathology. Data regarding patient demographics, lesion site, clinical presentation, and associated risk factors were collected. Biopsy specimens were processed using routine hematoxylin and eosin staining and examined microscopically to establish the final diagnosis. Results:Out of 120 patients, the majority were males (76) and most cases were observed in the 41–60 years age group. The buccal mucosa (30%) was the most commonly affected site followed by the tongue (23.3%). Non-healing ulcers (33.3%) were the most frequent clinical presentation. Histopathological examination confirmed oral squamous cell carcinoma in 88 cases, with well-differentiated OSCC being the most common type (38.3%). Tobacco chewing (43.3%) was identified as the most prevalent risk factor among the patients. Conclusion:Early biopsy plays a crucial role in the definitive diagnosis of oral squamous cell carcinoma. Timely histopathological evaluation of suspicious oral lesions facilitates early detection, accurate diagnosis, and prompt treatment planning. Early biopsy can significantly improve prognosis and contribute to better clinical outcomes in patients with oral cancer.
Keywords: biopsy, diagnosis, squamous, carcinoma, suspicious